Conference on transportation engineering proceedings of the conference held at the Central Hall, Westminster, London, June 22 to 24, 1965 (Institution of Civil Engineers, 1965)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in association with "Traffic Engineering and Control" on 22-24 June 1965.